THE MATERIAL CONDITIONS FOR ENTERING INTO MARRIAGE IN THE GRAND DUCHY OF LITHUANIA BEFORE THE 16TH CENTURY - Juozapaitienė, Rusnė (Teisė, 2015)
The interaction between the canon law and secular law governing the rules of one of the key social institutions, i.e. the family and marriage, is a relevant and significant subject. The impact of Christian canon law on the marriage institution in the Grand Duchy of Lithuania has not been sufficiently studied. The present article contains an analysis of the legal rules of marriage effective in the GDL and established in secular law, as well as their dynamics under the influence of the Christian canon law. The object of this research refers to the material conditions for entering into marriage in the Grand Duchy of Lithuania before the 16th century, and the impact of Christian canon law on their development.Before introduction of Christianity, the marriage in the GDL was likely to be formed based on the customary law. Once Lithuania accepted christening in 1387, the Grand Duchy of Lithuania became a Christian country where the Orthodox and Catholic canon law applied across its entire territory. There was a period when marriage could be formed both under the customary and canon law, since the Christianity and new law gained ground in the society only gradually. For instance, the Orthodox Church demanded that marriage with the first wife should be legalised, i.e. repeatedly formed at church with the aim of banning bigamy. The Christian canon law is recognised as one of the sources for the Statutes of Lithuania which were the main legal code of the GDL in the 16th century.The fundamental preconditions for entering into marriage in the Grand Duchy of Lithuania were a free will of future spouses, adequate marriageable age, the principle of monogamy, absence of consanguinity and affinity, the same religion of future spouses, and a mental state. The canon law altered understanding of the principle of a free will of marrying couples, and most likely as a result of the influence of canon law, the marriageable age of women was reduced to 13 years of age. The requirement regarding one’s mental state appeared under the influence of the canon law. The Christian moral principles did not tolerate intermarriage between close relatives or even their intimate relationships which used to be permitted in the period of customary law.Some conditions for marriage were differently treated by the Orthodox and Catholic canon law, e.g. unlike the Catholic canon law, the Orthodox canon law effective in the GDL required a parental consent as a mandatory precondition to form a valid marriage, and did not recognise secret marriages. A sexual intercourse mandatory under the Catholic canon law was not considered necessary to enter into valid marriage under the Orthodox canon law. Determining of the upper and lower marriageable age limits also varied.